First record of Cladosporium oxysporum isolated of tomato plant roots and control it using some factors of induce systemic resistance - Jaefar, Ola H. (Journal of Kerbala for Agricultural Sciences, 2018)
This study aimed to isolate and diagnose the causal agents of tomato root rot disease and test its pathogenicity using plate method. The efficiency some of induction factors SA and the fungi T.harzianum and Chaetomium sp. were evaluated in control of the pathogens. The results showed that presence of the fungi: Cladosporum oxysporum, Fusarium spp. in the infected roots of tomato plants. The results of the pathogenicity test displayed that the fungus Cladosporium oxysporum reduced the germination rate of cabbage seeds to 35.55% and Fusarium spp to 42.22 % compared with the control (cabbage seeds only) that was 93%. Further identification of C. oxysporum fungus based on its molecular characteristics confirmed first record of this fungus causing root rot disease of tomato plant in Iraq. Also, the biological agents T. harzianum and Chaetomium sp. achieved high inhibition percentage against C oxysporum in PDA media. Additionally, the results showed that the treatment of the biological factor Chaetomium spp was the best in reduction of the root rot severity (8.33 %), followed by the treatment of the T. harzianum with salicylic acid spray (16.66%) while the treatments of T.harzianum and salicylic acid were 25% for each compared to the control ( C.oxysporum alone) that was 75%. All treatments demonstrated a significant increase in soft and dry weight of the root and root length compare with treatment C.oxysporum only.